Dancing in the Shadow of Religious Politics: Jokowi's Political Communication Model Against the Pandemic - Abdul Pirol; Aswan, Aswan; Samsul Rijal (State Islamic Institute of Bone, Indonesia, 2025)
This article examines how President Joko Widodo’s political communication model responded to and managed religious sentiment during the Covid-19 pandemic in Indonesia. Employing a descriptive qualitative approach, the study analyzes selected posts from President Jokowi’s official Instagram account using Norman Fairclough’s Critical Discourse Analysis framework, which emphasizes the dimensions of text, discursive practice, and social practice. The findings reveal that the intersection of politics and religion in the context of pandemic governance generated significant resistance from segments of religious communities, manifested in distrust of Covid-19 information, vaccine rejection, conspiracy narratives, and opposition to burial procedures following health protocols. In response, the Jokowi administration strategically incorporated religious language, symbols, and institutional religious authority, such as references to the Indonesian Ulama Council and the notion of halal vaccines, into its communication strategy. This approach sought to align public health policies with dominant religious values in Indonesian society. The study demonstrates that religious discourse functioned as an instrument of symbolic power to stabilize public opinion and increase compliance with state policies. Contributes to political communication scholarship by showing how religious instrumentalization can function as a pragmatic crisis communication strategy in a democratic yet highly faith-oriented society.